PUTUSAN VERSTEK DALAM PERKARA PERCERAIAN DI PENGADILAN AGAMA SAMARINDA - Imron, (The Juris, 2021)
Marriage is the bond of birth between a man and a woman as husband and wife with the purpose of forming a happy and eternal family (household) based on the Supreme Godhead. divorce is one of the reasons for the termination of the marriage outside the other cause of death and or upon the verdict as stated in Article 38 No. 1 of 1974 The Marriage Law. In practice, there are sometimes various problems in the divorce process that are filed by the wife or divorce application submitted by the husband through the religious court, so they must be terminated in verses. Whereas for the verdict of the verses which grant the lawsuit, they must fulfill conditions such as petitum not against the law and have sufficient reasons.